2012
DOI: 10.4269/ajtmh.2012.11-0321
|View full text |Cite
|
Sign up to set email alerts
|

Capillaria philippinensis in Upper Egypt: Has It Become Endemic?

Abstract: Abstract. The goal of this study was to present an overview of human infections with Capillaria philippinensis , a new emerging parasite in Upper Egypt. The study included 21 inpatients who had been admitted to the Assiut University Hospital. Patients suffered from intermittent abdominal pain, borborygmi, chronic diarrhea lasting for several weeks, and marked weight loss. Hypoalbuminemia and low serum levels of potassium, calcium, and sodium were detected in most patients. A stool examination was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Infection reports in children were scarce. Two sisters aged 8 and 12 years from El-Minia governorate were reported (El-Karaksy et al, 2004) while two boys aged 9 years old were reported from Assiut governorate (Attia et al, 2012). S. mansoni and A. duodenale showed the same prevalence rate (1.2%) in the present study.…”
Section: G Lamblia Followed Bysupporting
confidence: 65%
“…Infection reports in children were scarce. Two sisters aged 8 and 12 years from El-Minia governorate were reported (El-Karaksy et al, 2004) while two boys aged 9 years old were reported from Assiut governorate (Attia et al, 2012). S. mansoni and A. duodenale showed the same prevalence rate (1.2%) in the present study.…”
Section: G Lamblia Followed Bysupporting
confidence: 65%
“…Protein-losing enteropathy is a complication frequently manifested in the intestinal capillariasis [16-18]. It is a result of direct mucosal invasion by the adult worms, which is sometimes exacerbated by the host inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Whether it was imported from the Philippines with imported live fish stock used to begin fish farms, or we just have our own strain in Egypt (Amin et al, 2011;Attia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the year 2002, El-Dib and Doss (2002) reported 44 cases, with 7 deaths, and later, Amin et al (2011) reported 8 new cases from BeniSweif, and Attia et al (2012) reported 21 cases from Assuit Governorate. The last 3 studies reported the infection in Upper Egypt.…”
Section: Introductionmentioning
confidence: 96%